JOURNAL ARTICLE WRITING TRAINING FOR ENGLISH TEACHERS IN LANDAK DISTRICT - Riyanti, Dwi; Gatot Sutapa Yuliana, Yohanes; Sada, Clarry; Sudarsono, Sudarsono (LPPM Univ. Ibn Khaldun Bogor, 2023)
As part of the Tri Dharma of Higher Education, the community service team of lecturers in the Master of English Education Study Program in 2022 conducted Community Service activities in Landak Regency, one of the regencies in West Kalimantan. This community service aimed to train English teachers regarding journal article writing that can be published in local and national journals. This activity was done based on good intentions to help teachers in Landak Regency, which is relatively far from the Capital City of West Kalimantan Province, to improve their professionalism as teachers who not only teach but also publish and manage their ranks. The current community service targeted English teachers at the elementary, junior high, and high school levels using the method of exposure accompanied by questions and answers with resource persons who have experience in the world of research and publication in both national and international journals. The number of participants who participated in this activity was 36, consisting of English teachers at all levels of education. Although the targets were elementary to high school teachers, there were two lecturers. The result of the community service indicates that the training was helpful for the participants.